REVITALIZATION OF RUPBASAN IN THE OPTIMIZATION OF ASSET MANAGEMENT OF CORRUPTION FOLLOWING RESULTS - Antok Kurniyawan (Legal Standing : Jurnal Ilmu Hukum, 2020)
Measuresi toi eradicatei corruptioni arei noti onlyi focusedi oni handlingi casesi onlyi buti Alsoi thei handlingi ofi evidencei asi ani importanti parti ofi creatingi justicei andi legali certainty.i Rupbasan'si confiscatedi asseti managementi Obtainedi fromi thei Corruptioni Eradicationi Commissioni isi currentlyi noti runningi optimally.i Alli aspectsi relatedi toi thei managementi ofi confiscatedi objectsi roommatesi shouldi bei Carriedi outi byi Rupbasani byi Reviewsi theiri dutiesi andi functionsi toi buildi ai mechanismi fori managingi assets,i thei resultingi fromi criminali acts,i asi statedi ini thei Criminali Procedurei Codei ini creatingi ai checki andi balancei processi fori lawi enforcement,i hasi noti yeti beeni fulfilledi Accordingi toi thei mandatei ofi thei law.i Thisi researchi willi contributei ini thei formi ofi ai newi viewi ofi strategici policymaking,i especiallyi ini thei fieldi ofi lawi isi directedi ati improvingi thei organizationi toi Realizei thei confiscationi ofi confiscatedi assetsi managementi byi thei provisionsi ofi thei lawi Juridicali analysisi usingi empiricali methods.i Thisi studyi aimsi toi describei thei currenti managementi systemi ini Rupbasan,i analyzei thei problemsi thati occur,i andi providei inputi throughi innovationi revitalizationi ofi Rupbasani toi maximizei thei managementi ofi confiscatedi assets,i resultingi fromi actsi ofi corruption.i Deviationsi toi thei provisionsi regardingi thei managementi ofi confiscatedi assetsi asi ai resulti ofi thei limitationsi andi discrepanciesi ini thei worki processi ofi Rupbasan,i toi thei demandsi ofi ani increasinglyi growingi task,i Thusi raisingi thei urgencyi ofi thei revitalizationi ofi Rupbasani thei whichi musti bei donei Immediatelyi toi Realizei justicei andi legali certainty.